Neuromyelitis optic with positive Anti-AQP4 and Anti-SSA/Ro antibody - Riwanti Estiasari; Salsabila Firdausia; Dewi Wulandari; Kartika Maharani; Freddy Sitorus; David Pangeran; Darma Imran (MDPI AG, 2019)
Neuromyelitis Optic (NMO) is an inflammatory disorder involving central nervous system which often co-exists with other autoimmune diseases such as Sjögren's syndrome (SS). NMO manifestation could precede or follow SS, but the role of anti-SSA in the pathogenesis of NMO remains unclear. We present a case of NMO with anti-AQP4 anti-SSA antibody positive. A-44-year-old female presented with right side weakness. The symptoms began with numbness that improved spontaneously. She also complained pain and dry sensations on her eyes. Schirmer test on her left eye, antinuclear antibody (ANA) and anti- SSA antibody were positive. Cervical MRI revealed intramedullary lesion on T2- weighted-image at C2-C5 level. She was diagnosed as NMO with positive anti- AQP4 and probable SS. She received 1g methylprednisolone for 5 days proceeded with mycophenolic acid. One-year observation showed clinical improvement. Systemic autoantibodies must substantially be evaluated in NMO. Comprehensive diagnosis and providing appropriate immunosuppressant might prevent further disability and relapse.